Análisis de sostenibilidad del régimen impositivo simplificado y determinación de una vida útil óptima. Caso Guayaquil, período 2012 - 2014 - Haro Orellana, José Francisco (2016)
Simplified tax systems have as main idea to carry people who are part from informal economy in a society to the formal practicing of their economics activities. In Ecuador, RISE from its birth has been important on the generation about taxing culture, nevertheless there is important to analyze how long is possible to maintain a fiscal tool which easily seen, does not meet the universal objective of taxation, incomes collection and, on the other hand, its continued existence accuses the need to implement control process as a labor of tax management. This thesis aims to determine the optimal duration of simplified taxation in Ecuador, according to the inclusion and exclusion or waiver by taxpayers.